Kinerja Sosial Perusahaan dan Kinerja Keuangan Perusahaan yang Diukur Menggunakan Tobin’s q - Edbert Eduardus (Business Accounting Review, 2016)
This study aimed to examine and to prove the reciprocal relationship between corporate social performance and corporate financial performance. Corporate social performance using a proxy Sustainability Reporting Index assessed by using criteria guideliness of GRI version 3.1. The corporate financial performance of this study was measured by using Tobin's q. This study also used control variables of firm size and leverage. This study tested the 30 listed companies on IDX with minimal once published a sustainability reporting between 2008 - 2014. The results of this study found that between corporate social performance and corporate financial performance had a reciprocal relationship.